If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6c + -7 = 71 Reorder the terms: -7 + 6c = 71 Solving -7 + 6c = 71 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 6c = 71 + 7 Combine like terms: -7 + 7 = 0 0 + 6c = 71 + 7 6c = 71 + 7 Combine like terms: 71 + 7 = 78 6c = 78 Divide each side by '6'. c = 13 Simplifying c = 13
| 12-3y=6y-6 | | 5x-9y=z | | 7(y-80)=91 | | 7p+10=-2p+55 | | 15other= | | 6y+5-3-15y=10 | | 6+x=46 | | x^2+4ix+1=0 | | 32+2n=84 | | -8-3k/2=11 | | 45*57+8-74= | | 0.6x+7=-6 | | -1145=-866-v | | 2n^2-2n-220=0 | | 4z+12-2z=2 | | 0.6x+7=8 | | 6.2/12.71 | | -11t=5-6t | | -14.5(-1.5)=-31.5 | | 6z+8=-22 | | 19÷1/3 | | 3/4x=a | | 8-2x=-24 | | 11=23-2j | | 19=1/3p | | 6n-2=4n+8 | | 17=-2(3h-4) | | 8(4a+2b)= | | 5z+9=6z | | Sin(35)=4/x | | 10(s+6)=100 | | 9/c=6/10 |